2013
DOI: 10.1186/1471-2458-13-1183
|View full text |Cite
|
Sign up to set email alerts
|

Why parents refuse childhood vaccination: a qualitative study using online focus groups

Abstract: BackgroundIn high income countries, vaccine-preventable diseases have been greatly reduced through routine vaccination programs. Despite this success, many parents question, and a small proportion even refuse vaccination for their children. As no qualitative studies have explored the factors behind these decisions among Dutch parents, we performed a study using online focus groups.MethodsIn total, eight online focus groups (n = 60) which included Dutch parents with at least one child, aged 0–4 years, for whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 28 publications
7
141
0
13
Order By: Relevance
“…Among the main factors that discourage parents from having their babies immunized is the perception that the child is not vulnerable (Harmsen et al, 2013). Some respondents who had older children who were not immunized and did not contract notable communicable diseases erroneously assumed that susceptibility to disease follows a predictable pattern; this antecedent effect can lead them to regard immunization as pointless.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main factors that discourage parents from having their babies immunized is the perception that the child is not vulnerable (Harmsen et al, 2013). Some respondents who had older children who were not immunized and did not contract notable communicable diseases erroneously assumed that susceptibility to disease follows a predictable pattern; this antecedent effect can lead them to regard immunization as pointless.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that participants believed that vaccine preventable diseases are not dangerous [147,148,150] but instead are beneficial for child development [149,150]. Some also believed that risks of vaccination outweigh benefits [147,150,154]. Studies found that interviewed participants reported inadequate information and evidence [143,144,147,153] and disagreements between experts on vaccine safety [144].There were beliefs that vaccines do not work or have a short duration of protection [143,146,150,154], supporting the perception that vaccines are not useful [146,153,154].…”
Section: Childhood Vaccinationmentioning
confidence: 98%
“…Eleven articles studied concerns about childhood vaccination in general [143][144][145][146][147][148][149][150][151][152][153][154]. The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The groupness evident in these studies -and others -pertains to people orienting their attitudes based on those around them (Benin et al, 2006, Harmsen et al, 2013. While historically this has relied upon physical proximity or tangible relationships, the internet and social media have opened up avenues for geographically disaggregated individuals to connect around ideas and practices (Sobo et al, 2016).…”
Section: A Critical Appraisal Of Literature Pertaining To Vaccine Hesmentioning
confidence: 99%